Suffer or Survive: Decoding Salt-Sensitivity of Lemongrass and Its Implication on Essential Oil Productivity - Mukarram, Mohammad; Khan, M. Masroor A.; Zehra, Andleeb; Petrik, Peter; Kurjak, Daniel (Frontiers in Plant Science, 2022)
The cultivation of lemongrass (Cymbopogon flexuosus) crop is dominated by its medicinal, food preservative, and cosmetic demands. The growing economy of the lemongrass market suggests the immense commercial potential of lemongrass and its essential oil. Nevertheless, the continuous increase of the saline regime threatens the growth and productivity of most of the plant life worldwide. In this regard, the present experiment explores the salt sensitiveness of the lemongrass crop against five different levels of salt stress. Metabolomic analyses suggest that lemongrass plants can effectively tolerate a salt concentration of up to 80 mM and retain most of their growth and productivity. However, extreme NaCl concentrations (≥160 mM) inflicted significant (α=0.05) damage to the plant physiology and exhausted the lemongrass antioxidative defence system. Therefore, the highest NaCl concentration (240 mM) minimised plant height, chlorophyll fluorescence, and essential oil production by up to 50%, 27%, and 45%. The overall data along with the salt implications on photosynthetic machinery and ROS metabolism suggest that lemongrass can be considered a moderately sensitive crop to salt stress. The study, sensu lato, can be used in reclaiming moderately saline lands with lemongrass cultivation converting such lands from economic liability to economic asset.